Integrating marine ecosystem conservation and ecosystems services economic valuation: implications for coastal zones governance - Ferreira, Ana Margarida (2018)
This paper presents a preliminary attempt to estimate the awareness and value that society gives to the maintenance and protection of marine protected areas, linking the ecological and economic value scale assigned to the study. To accomplish this, we took as illustrative example the Biophysical Interest Zone of Avencas (ZIBA), in Portugal. The ZIBA spans over one ha and its coastal ecosystems present a very rich biodiversity, providing several socio-economic opportunities to society. To estimate the value that society attributes to this area we conducted a contingent valuation exercise, considering two different aspects: 1) the direct economic value that people state to conserve the ecosystem and 2) the willingness to contribute through the allocation of hours of voluntary work to its conservation. The values obtained indicate the dependence and importance of this ecosystem to local population (willing to pay to conserve it of 60 € per household per year and willing to give 3h of voluntary work per year). The proximity of the local population to the protected area increases the willing to pay for its conservation; this could reveal a good local indicator of ecosystem valuation. This valuation exercise highlights the importance of coastal ecosystem services to society and draws attention to the benefits that local populations derive from those systems. These results have also implications in future governance actions regarding protected areas, as well as to justify for sustainable investments in coastal management efforts, to sustain the flow of coastal ecosystem services for current and future generations.